HAK KREDITOR UNTUK MENGGUGAT PERUSAHAAN EFEK DI PENGADILAN NIAGA - Chandra Yusuf (Jurnal HUKUM BISNIS, 2020)
Judges in the Commercial Court can use different articles in the Law (Law) Number 37 of 2004 concerning Bankruptcy and Postponement of Obligations of Debt Payment (KPKPU). The behavior of judges in deciding cases becomes inconsistent because the articles in the Act regulate the opposite. Article 2 paragraph (1) and Article 2 paragraph (4) of the KPKPU Law stipulates that 2 (two) creditors can sue the debtor bankruptcy in the Commercial Court and Creditors cannot sue the Debtor bankruptcy, unless the Capital Market Supervisory Agency (Bapepam) sues the Securities Company . In deciding bankruptcy cases, judges must have a consistent legal basis to determine the articles used in the same case. To overcome this problem, the judge has two choices to use the basis, namely Jeremy Betham's theory of benefit and individual rights based on the thinking of Albert Venn Dicey, KC, FBA. From the results of the analysis, the use of individual rights takes precedence. Claiming bankruptcy by individuals to securities companies solves the problem more. Keywords: Bankruptcy, Securities Companies, Individual Rights